Experimental study on transient interface in unconfined coastal aquifer - Titus, Jovan Soosaipillai; Gupta, Ashim Das; Suphat Vongvisessomjai; Jensen, Niels Einar; The Government of Netherlands (Bangkok : Asian Institute of Technology, 1989)
Study on the transient interface phenomenon in coastal aquifers needs the solution of non linear partial differential equations . The transient phenomenon is due to changes in fresh water flow rate as well as due to tidal action . The changes in flow rate can be from natural process or by man induced pumping. Also when pumping is introduced in the intruded region, interface upcones in the vicinity of pumping. Transient movement of interface with upcoming under pumping condition is investigated based on experimental observation. A semi-empirical equation based on Ghyben-Herzberg (G-H) assumption describing the interface movement during pumping in a phreatic coastal aquifer is presented. The effect of pumping in the system considered, is incorporated in t he mode l in terms of t he depth of the interface below the mean sea l eve l (MSL) and as t he boundary condition at the pumping location . Experiments we re carried out in a vertical Hele-Shaw model at different operating conditions to obtain the boundary condition at the pumping location and at the outflow face. The additional length of intrusion obtained using these boundary conditions have been compared with the intrusion length obtained from the experiments. The profile of the interface at different times is obtained by solving the continuity equation for fresh water flow in t he intruded zone, using the boundary conditions obtained from the experimental studies and the computed profiles are then compared with the experimental ones . Finally from the experimental results, relationships in non-dimensional forms for t he interface position below the MSL at the pumping location at any time and time of depletion of storage are obtained in terms of t he other relevant parameters are provided.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1989
Keywords: Aquifers